Effect of Some Fungal Strains on Seed Germination of Faba Bean var. minor in Libya - El-Gali, Zahra Ibrahim; Saad, Amina Abdul-Hamied (Al-Mukhtar Journal of Sciences, 2021)
This research was conducted during the season 2019-2020 at the plant pathology laboratory-Faculty of Agriculture-Omar Al-Mukhtar University, to study the effect of some isolates of fungi Botrytis cinerea, Macrophomina phaseolina, Sclerotinia sclertiorum, Rhizoctonia solani, and Trichoderma harzianum on germination percentage, germination speed and root disease levels in seeds of Vicia faba minor variety in vitro. Seeds were incubated after sterilization and planting on WA media (1%) in Petri dishes inoculated with the fungi. The experiment recorded significant differences in germination ratio, germination speed, and level of disease. The best germination (91.7%) was recorded in T. harzianum treatment but not more than the control treatment (100%), and the minimum germination (25%) was in seeds treated with M. phaseolina and R. solani. Germination speed was higher (3.1) in Trichoderma periphery than that in control and pathogenic fungi treatments. While the disease level reached 4.8 in R. solani and it recorded 0 in Trichoderma and control treatments. The results presented in this paper demonstrate the seed treatment with T. harzianum can be beneficial to enhance Faba bean seed germination as well as reduce delayed germination.